Oenothera oehlkersii Kappus ex Rostański - a new evening-primrose species in Polish flora - Wolanin, Mateusz; Woźniak, Monika (Biodiversity: Research and Conservation, 2012)
Oenothera oehlkersii Kappus ex Rostański - a new species of Polish flora - was found on the Przemyśl Foothills. The species is a hybrid between Oe. glazioviana Micheli in Mart. and Oe. suaveolens Desf. ex Pers. In this paper, authors present some features useful in recognizing the parental species and the hybrid one.